A highly active mineral-based ice nucleating agent supports in situ cell cryopreservation in a high throughput format. Issue 199 (8th February 2023) - Daily, Martin I.; Whale, Thomas F.; Kilbride, Peter; Lamb, Stephen; John Morris, G.; Picton, Helen M.; Murray, Benjamin J.
Abstract : Cryopreservation of biological matter in microlitre scale volumes of liquid would be useful for a range of applications. At present, it is challenging because small volumes of water tend to supercool, and deep supercooling is known to lead to poor post-thaw cell viability. Here, we show that a mineral ice nucleator can almost eliminate supercooling in 100 µl liquid volumes during cryopreservation. This strategy of eliminating supercooling greatly enhances cell viability relative to cryopreservation protocols with uncontrolled ice nucleation. Using infrared thermography, we demonstrate a direct relationship between the extent of supercooling and post-thaw cell viability. Using a mineral nucleator delivery system, we open the door to the routine cryopreservation of mammalian cells in multiwell plates for applications such as high throughput toxicology testing of pharmaceutical products and regenerative medicine.